2018
DOI: 10.1016/j.bja.2018.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Safety and clinical effect of i.v. infusion of cyclopropyl-methoxycarbonyl etomidate (ABP-700), a soft analogue of etomidate, in healthy subjects

Abstract: NTR4735.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…5 Notable side effects of ABP-700 include the occurrence of excitatory phenomena such as involuntary muscle movements, tachycardia, and tachypnea. 5,8 Although recent preclinical studies showed that CPM-acid can inhibit the GABA A receptor, a potential mechanism for seizure induction, 9 this effect was only seen at concentrations two orders of magnitude greater than those achieved clinically.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…5 Notable side effects of ABP-700 include the occurrence of excitatory phenomena such as involuntary muscle movements, tachycardia, and tachypnea. 5,8 Although recent preclinical studies showed that CPM-acid can inhibit the GABA A receptor, a potential mechanism for seizure induction, 9 this effect was only seen at concentrations two orders of magnitude greater than those achieved clinically.…”
Section: Discussionmentioning
confidence: 99%
“…As we developed the BIS model, we found that the initial model did not have a satisfactory fit. Based on our observation that increased BIS values were reported in subjects experiencing severe involuntary muscle movements, 5,8 we then decided to separate the BIS effect into a suppression Recirculation Model of ABP-700…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations